Application of Lecture Method In Learning Akidah Akhlak In Class VIII (A) SMP Muhammadiyah 56 Binjai - Erli Rahmayani; Nurhalima Tambunan (Program Pascasarjana UIN Sumatera Utara, 2023)
This research aims to explore: (1) Application of the lecture method in learning moral beliefs in class VIII (A) SMP Muhammadiyah 56 Binjai, (2) solution for applying the lecture method in learning moral beliefs in class VIII SMP Muhammadiyah 56 Binjai. This research uses a descriptive qualitative approach. The data sources in this research are the school principal, teachers of morals and students. The data collection technique uses observation, interviews and documentation. The data analysis techniques used are data reduction, data display and data conclusion drawing. The results of research on the application of the lecture method in learning moral beliefs in class VIII SMP Muhammadiyah 56 Binjai, namely that the teacher said that using the lecture method was very easy to implement, but sometimes students tended to be passive in class. The solution for applying the lecture method in moral belief lessons in class VIII SMP Muhammadiyah 56 Binjai is to make the lesson material structured, use props when lecturing and explain using terms that can be understood by students.Penelitian ini bertujuan untuk mengeksplor: (1) Penerapan metode ceramah dalam pembelajaran akidah akhlak di kelas VIII (A) SMP Muhammadiyah 56 Binjai, (2) Solusi penerapan metode ceramah dalam pembelajaran akidah akhlak di kelas VIII SMP Muhammadiyah 56 Binjai. Penelitian ini menggunakan pendekatan kualitatif yang bersifat deskriptif. Sumber data dalam penelitian ini adalah kepala sekolah, guru mata pelajaran akidah akhlak dan peserta didik. Teknik pengumpulan datanya menggunakan observasi, wawancara dan dokumentasi. Teknik analisa data yang digunakan adalah reduksi data (data reduction), penyajian data (data display), dan penarikan kesimpulan data. Hasil dari penelitian penerapan metode ceramah dalam pembelajaran akidah akhlak di kelas VIII SMP Muhammadiyah 56 Binjai yaitu guru mengatakan bahwa penggunaan metode ceramah sangat mudah dijalankan, namun terkadang siswa cenderung bersikap pasif didalam kelas. Solusi dalam penerapan metode ceramah pada pelajaran akidah akhlak di kelas VIII SMP Muhammadiyah 56 Binjai yaitu buatlah materi pelajaran secara terstruktur, gunakan alat peraga waktu berceramah dan menjelaskan dengan menggunakan istilah-istilah yang dapat dipahami oleh peserta didik.